Dislocation in Translation - Sakai, Naoki (TTR)

(untitled) (Association canadienne de traductologie, 2009)
My inquiry into translation is, first of all, concerned with a regime that postulates translation as something representable, and then, with the task of historicizing that regime. The definition of translation as the “transfer of the message from one language into another” leads to the supposition that languages are separate and discrete unities. But what might translation be if we suppose that this is not the case and that one language cannot be easily distinguished from another? The Jakobsonian concept of interlingual translation or “translation proper” fails to take into account the ambiguity inherent in the translator’s position: who and where is the translator in relation to the source and target texts? Being neither addresser nor addressee the translator becomes a “subject in transit.” If translation is understood as simply the transfer of an invariant message from one language to another, the ambiguity of the translator’s positionality is suppressed and with it the idea of translation as a poietic social practice that institutes a relation at the site of incommensurability. When this occurs, translation is replaced by the “representation of translation” and comes to be seen as a form of communication between two fully circumscribed language communities. It was this particular representation of translation which gave rise to the possibility of identifying the unity of ethnic or national language with another language unity. By this “schema of co-figuration” an ethnic‑linguistic community becomes a “geo‑body” on which national sovereignty is built. Two nations represented as equivalent and alike can be viewed as conceptually different, a difference construed as a specific difference. The co‑figuration of “the West and the Rest” is an example of the resultant typical binary oppositions: “the West” constitutes itself by positing everything else as “the Rest” allowing one term to be evaluated as superior to the other. The identification of “modern” with “the West” changed how people organized historical experience; movement in time came to be associated with movement from periphery to centre. Historically, how we represent translation prescribes how we imagine national communities and ethnic identities.